2022
DOI: 10.1002/pds.5551
|View full text |Cite
|
Sign up to set email alerts
|

Quality of rheumatoid arthritis recording in United Kingdom Clinical Practice Research Datalink Aurum

Abstract: Purpose While several studies have assessed quality and completeness of recording acute medical events in Clinical Practice Research Datalink (CPRD) Aurum, evaluation of additional chronic conditions is warranted. Methods We selected patients with a first diagnosis of rheumatoid arthritis (RA) coded in their CPRD Aurum record between 2005 and 2019. We assessed quality of RA diagnosis by evaluating additional information in the patient record that would corroborate the diagnosis. We report recording of diagnose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Since then, work to assess the quality and completeness of recording in CPRD Aurum has been undertaken to describe its characteristics, strengths, and limitations related to its suitability for use in medical research. [2][3][4][5][6][7] The results presented in our companion paper indicate that the recording of breast cancer diagnoses, treatments, and prescription drugs in CPRD Aurum were of similarly high quality compared to CPRD GOLD. 8 This study was conducted to extend the assessment to comparison with external linked data sources.…”
Section: Introductionmentioning
confidence: 85%
“…Since then, work to assess the quality and completeness of recording in CPRD Aurum has been undertaken to describe its characteristics, strengths, and limitations related to its suitability for use in medical research. [2][3][4][5][6][7] The results presented in our companion paper indicate that the recording of breast cancer diagnoses, treatments, and prescription drugs in CPRD Aurum were of similarly high quality compared to CPRD GOLD. 8 This study was conducted to extend the assessment to comparison with external linked data sources.…”
Section: Introductionmentioning
confidence: 85%
“…In our previous short report, we found that codes expected for monitoring and treatment of RA were routinely recorded in CPRD Aurum. 21 Our current study provides a more thorough description of RA-related data captured in the CPRD Aurum patient record, as well as a side-by-side comparison to the equivalent data recorded in CPRD GOLD. Overall, the recording of diagnoses, prescription drugs and labs in the year before and the year after first RA diagnosis were similar between CPRD Aurum and CPRD GOLD.…”
Section: Discussionmentioning
confidence: 99%
“… 12 CPRD GOLD has been successfully used in many studies of rheumatoid arthritis (RA) and other chronic outcomes, 13–20 but assessment of data recording for RA in CPRD Aurum is limited to our previous short report that found that codes expected for monitoring and treatment of RA are routinely recorded in CPRD Aurum, without comparison to an external data source. 21 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 4–6 Other studies have reported high internal consistency between diagnoses and presence of relevant clinical codes (labs, prescriptions, and other clinical care) for type 2 diabetes, hyperlipidemia, anemia, 7 and RA. 8 Indication for use of benign prostatic hyperplasia drugs was present for a large proportion of patients, suggesting that CPRD Aurum may adequately capture this important detail for drugs prescribed by GPs. 9 Finally, the number of recorded prescriptions for the most common antibiotics was similar in CPRD GOLD and CPRD Aurum, 10 though drugs prescribed in specialty care may have low capture.…”
Section: Key Findingsmentioning
confidence: 99%